Dynamics of Job Security of Journalists in the Political Economy of Nigeria and the Future of Journalism Practice - Kingsley Onah; Tsegyu Santas; Kelvin Inobemhe (Universitas Multimedia Nusantara, 2025)
The study was conducted to examine the existential issues in Nigeria’s political economy and the interconnectedness with the job security of practising and aspiring journalists and the future of journalism practice in Nigeria. It is a conceptual research with retrospective review and analysis of trends based on documented virtual and physical secondary sources of data collection such as books, journals, newspapers. It showed that the political economy of the country has been a mixed bag of undulating experience characterised by uncertainties of political policies, decisions and actions that have adversely impacted the economy thereby creating distressing working and living conditions for media organisations, journalists and by extension, the Nigerian workers. In addition, the study demonstrated that beyond journalism practice, the reality of the political economy was critical to determining the availability of an enabling environment for continuity with consequent concerns of job security for journalists both as employees and employers in the line of duty and what the future holds for them in the practice. While it concluded that the political economy has posed serious threat for journalism to thrive as expected, it recommended that political actors should create the enabling environment for guaranteed job security for journalists in Nigeria.